Developing capacity through co-design: the case of two municipalities in rural South Africa. Issue 2 (3rd April 2019) - Jacobs, Carl; Rivett, Ulrike; Chemisto, Musa
ABSTRACT: In South Africa, the socio-economic development of rural communities lags the furthest. One of the factors contributing towards this is the incapacity of local municipalities to deliver basic services. This paper discusses how municipal capacity can be improved through an ICT system that is designed and implemented using co-design. In a case study of two South African rural municipalities, capacity was assessed before and after an ICT system was implemented. Using the co-design methodology, stakeholders became part of the design team. The study empirically showed that capacity increased in both municipalities after the ICT system was implemented. The resulting developmental change manifested itself in the sectors of governance, engagement, human resource management, institutional memory, and access to information. The findings showed that understanding the context and current capabilities of stakeholders and investing time in the design of the ICT system resulted in greater impact than literature previously suggested.